Dynamical control in a prethermalized molecular ultracold plasma: Local dissipation drives global relaxation - Ruoxi Wang; Amin Allahverdian; Smilla Colombini; Nathan Durand-Brousseau; Kevin Marroquín; James Keller; John Sous; Abhinav Prem; Edward Grant (Physical Review Research)
Prethermalization occurs as an important phase in the dynamics of isolated many-body systems when coupled degrees of freedom relax in a subspace separated from a state of complete thermodynamic equilibrium by a gap in energy or other conserved quantity. Slow equilibration from a prethermal phase can localize the dynamics of natural and model systems despite high dimensionality and limited disorder. Here, we report the signature of an enduring prethermal regime of arrested relaxation in the molecular ultracold plasma that forms following the avalanche of a state-selected Rydberg gas of nitric oxide. For a wide range of initial conditions, this system enters a critical phase in which a density of NO^{+} and electrons balances a population of Rydberg molecules. Electron collisions mix orbital angular momentum, scattering Rydberg electrons to states of very high ℓ. The rapid predissociation of molecules in states of low-ℓ purifies this high-ℓ ensemble. The angular momentum barrier that separates NO^{+} ions and electrons creates an extraordinary gap between the plasma states of n≈ℓ, with measured n>200 and penetrating states of ℓ=0,1, and 2. Evolution to a statistically equilibrated state of N and O atoms cannot occur without Rydberg electron penetration, and this gap blocks relaxation for a millisecond or more. A weak radiofrequency (RF) field drives ℓ-mixing electron collisions that erase this gap, causing wholesale dissipation. Remarkably, a local quantum-state transition promoting an exceedingly small fraction of the molecules in the prethermalized ensemble to a predissociative state also acts with a global effect, driving the entire system to a dissipative equilibrium. Using the Lindblad master equation, we illustrate qualitatively similar dynamics for a toy model of an open quantum system that consists of a localized set of spins on which dissipation acts at a single site as a gateway to equilibrium.